Short‐term effects of a severe drought on avian diversity and abundance in a Pampas Agroecosystem. (19th August 2019) - Weyland, Federico; Baudry, Jacques; Ghersa, Claudio
Abstract: Agroecosystems are naturally variable at different scales showing strong environmental variations through time and in space. Therefore, temporal dynamics should be taken into account to understand the species‐habitat relationship and provide information for biodiversity management. Droughts are climatic events that introduce variations in environmental conditions by reducing food resources and are increasing in severity and frequency due to global climate change. In 2008, a severe drought occurred in the argentine Pampas, which allowed us to test its short‐term effect on avian diversity patterns according to different land uses. Also, we could test how variations in net primary productivity affected bird populations and explore the usefulness of this ecological process as an indicator of ecosystem service supply applicable to different ecological contexts. We surveyed bird diversity in two consecutive years (2007–2008) in the Rolling Pampas of Argentina, and we assessed environmental attributes at two spatial scales. We explored the relationship between bird diversity and an ecosystem services provision index (ESPI) that uses a proxy of net primary productivity and its intra‐annual variation to test its adequacy in the changing conditions, we conducted our surveys. Results showed that drought affected negatively both species richness and abundance as a consequence of net primary productivity reductions. There was not a clear association of diversity changes with land use, and it is probable that the effect of drought is a complex combination of productivity, land use and spatial scale. ESPI proved robust in front of the environmental changes, and its predictive capacity was better at larger scales. These results are promising for the assessment of ecosystem services provision in a context of global climate changes. Abstract in Spanish is available with online material. Resumen: Los agroecosistemas son naturalmente variables a diferentes escalas mostrando fuertes variaciones ambientales en el tiempo y el espacio. Por lo tanto, la dinámica temporal debería ser tenida en cuenta para entender la dinámica de las relaciones especie‐hábitat y proveer información para el manejo de la biodiversidad. Las sequías son eventos climáticos que introducen variaciones en las condiciones ambientales al reducir los recursos alimenticios y están incrementándose en severidad y frecuencia debido al cambio climático global. En 2008 una sequía severa afectó a las Pampas de Argentina, lo que nos permitió estudiar su efecto a corto plazo sobre los patrones de diversidad de aves de acuerdo a diferentes usos de la tierra. También pudimos estudiar cómo las variaciones en productividad primaria neta afectaron las poblaciones de aves y explorar la utilidad de este proceso ecosistémico como un indicador de provisión de servicios ecosistémicos aplicable a diferentes contextos ecológicos. Relevamos la diversidad de aves en dos años consecutivos (2007–2008) en la Pampa Ondulada de Argentina, y evaluamos atributos ambientales a dos escalas espaciales. Exploramos la relación entre diversidad de aves y el Indice de Provisión de Servicios Ecosistémicos (ESPI). Este índice usa un indicador de productividad primaria neta y su variación intra anual y probamos su adecuación a las condiciones ambientales cambiantes durante nuestros relevamientos. Los resultados mostraron que la sequía afectó negativamente tanto la riqueza de especies como la abundancia de individuos como consecuencia de reducciones en la productividad primaria neta. No huno una asociación clara en los cambios de diversidad con el uso del suelo, y es probable que el efecto de la sequía sea una combinación compleja de pruductividad, uso del suelo y escala espacial. El ESPI probó ser robusto frente a cambios en las condiciones ambentales y su capacidad predictiva fue mejor a escalas grandes. Estos resultados son promisiorios para la evaluación de la provisión servicios ecosistémicos en un contexto de cambio climático.